Influence of degradation medium on the partial dissolution of polyester textile sample - Clemented, Eligia D. (Philippine Engineering Journal)
Polymer degrades due to significant changes in its chemical structure, physical properties or appearances under specific environmental conditions. When polymer is exposed to solutions, swelling and dissolution govern the degradation process. Swelling or partial dissolution is characterized by the occurrence of cracks or stress fracture in the polymer fiber. In this study, the chemical resistance of polymer textile sample to partial dissolution or swelling was examined. The sample was exposed to solutions of different pH levels (NaHCO3-Na2CO3 buffer with a pH of 10.47; distilled water with a pH of 7.0 and HOAc-CaAc buffer with a pH of 4.67) for 142 hours. After soaking, this was the surface characteristics were examined with the use of a Scanning Electron Microscope. Although indications of the formation of cracks were found, negligible weight loss was observed. This implied the slow reactivity of the sample to the solution. The onset of polymer degradation accelerated as the test reagent deviated from neutrality either way.